Polyanion order controls liquid-to-solid phase transition in peptide/nucleic acid co-assembly - Gordon-Kim, Christella; Rha, Allisandra; Poppitz, George A.; Smith-Carpenter, Jillian; Luu, Regina; Roberson, Alexis B.; Conklin, Russell; Blake, Alexis; Lynn, David G. (Frontiers in Molecular Biosciences, 2022)
The Central Dogma highlights the mutualistic functions of protein and nucleic acid biopolymers, and this synergy appears prominently in the membraneless organelles widely distributed throughout prokaryotic and eukaryotic organisms alike. Ribonucleoprotein granules (RNPs), which are complex coacervates of RNA with proteins, are a prime example of these membranelles organelles and underly multiple essential cellular functions. Inspired by the highly dynamic character of these organelles and the recent studies that ATP both inhibits and templates phase separation of the fused in sarcoma (FUS) protein implicated in several neurodegenerative diseases, we explored the RNA templated ordering of a single motif of the Aβ peptide of Alzheimer’s disease. We now know that this strong cross- propensity motif alone assembles through a liquid-like coacervate phase that can be externally templated to form distinct supramolecular assemblies. Now we provide evidence that structured phosphates, ranging from complex structures like double stranded and quadraplex DNA to simple trimetaphosphate, differentially impact the liquid to solid phase transition necessary for paracrystalline assembly. The results from this simple model illustrate the potential of ordered environmental templates in the transition to potentially irreversible pathogenic assemblies and provides insight into the ordering dynamics necessary for creating functional synthetic polymer co-assemblies.